Implementação de um modelo de trinca discreta com redefinição da malha associado a modelos de dano escalar - Natália de Oliveira Assis (2023)
A discrete crack model with re-meshing via nodal duplication, based on scalar damage models,is implemented and applied for the nonlinear analysis of concrete. The implementation of this model aims to analyze the behavior of the material in the presence of cracking and describe the propagation of cracks. The damage models are used to describe the degradation process of the material, and after the material reaches a crack nucleation criterion, a geometric discontinuity is inserted in the finite element mesh. The redefinition of the mesh is performed through nodal duplication, thus allowing the adaptation of the mesh according to the propagation of the cracks. The model was implemented in the computational system INSANE (INteractive Structural Analysis Environment), which was developed in the Department of Structural Engineering at UFMG. Numerical simulations were performed to validate the proposed model.